PERAN BIMBINGAN KONSELING ISLAM DALAM MENUMBUHKAN AKHLAK DAN MORAL PADA SISWA - Fatia, Deska Nur; Khairunida, Dieni; Salsabila, Kaila; Ramadhona, Rena; Putri Dewi, Dyah Pitaloka; Yulia, Cici; Syarkawi, Syarkawi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
This study aims to analyze the coping strategies and mechanisms used by final year students at UHAMKA (Prof. Dr. Hamka University) in completing thesis writing. The research method used a qualitative approach with data collection techniques through indepth interviews and participatory observation. The research participants were final year students from various study programs at UHAMKA. The results showed that there were several coping strategies used by students in overcoming various challenges and stress that arose during the thesis completion process. These strategies include time management, social support from lecturers and peers, adaptation to pressure and deadlines, and balancing academic and non-academic life. This study also identified factors that influence students' selection of certain coping strategies. The findings of this study can provide a better understanding of the coping mechanisms used by students in facing challenges while completing their thesis, as well as provide input for educational institutions to improve support to students in completing their academic tasks.